NewsFraud-SC: A Dataset of News about Corruption Extracted from SC Multiple Portals - de Souza, Ana Clara Stupp; Dorneles, Carina F. (Anais do Dataset Showcase Workshop (DSW); 2026: Anais do VIII Dataset Showcase WorkshopDO - 10.5753/dsw.2026.249443, 2026)
This article presents NewsFraud-SC, a dataset composed of news articles about illicit activities in the public sector, originating from multiple news portals in the state of Santa Catarina. With a total volume of 70 MiB, the dataset was constructed using an automated collection pipeline that integrates web scraping techniques, content cleaning via readability algorithms, and Named Entity Recognition (NER). Each record in the dataset is structured in JSON format, containing detailed metadata such as source, URL, and date, as well as previously extracted entities, including people, organizations, locations, and monetary values involved in the reported incidents. The work describes the collection methodology, descriptive statistics of the corpus, highlighting the distribution of topics and the density of entities. With 10,913 extracted entities and well-defined metadata, this corpus allows researchers to bypass the traditional data engineering bottleneck typically associated with web scraping and manual content cleaning. As a scientific contribution, the dataset is made available to the academic community, aiming to foster research in the extraction of complex relationships and government transparency technologies.